1999
DOI: 10.1034/j.1399-6576.1999.430603.x
|View full text |Cite
|
Sign up to set email alerts
|

Block of the brachial plexus branches by the humeral route. A prospective study in 503 ambulatory patients. Proposal of a nerve‐blocking sequence

Abstract: This study shows that the nerve block at the humeral canal is an efficient and safe technique. Considering the onset times of nerve blocks, the following sequence for blockade can be recommended: median, ulnar, radial, musculocutaneous, medial (brachial and antebrachial) cutaneous nerves. The selective blockade of the main nerves of the upper limb at the humeral canal can be recommended for surgery of the forearm and the hand in the ambulatory patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 9 publications
1
16
1
1
Order By: Relevance
“…One of the explanations may be related to the duration of the evaluation, which was 30 minutes in the present study and only 20 minutes in the one by Rodriguez et al 15 The success rate reported here is similar to those already published for an axillary approach using a multiple injection technique, providing that an equivalent definition of the success was used. [16][17][18] This observation is important since it is recognized that compared with a multiple injection technique, a single injection technique may cause less pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…One of the explanations may be related to the duration of the evaluation, which was 30 minutes in the present study and only 20 minutes in the one by Rodriguez et al 15 The success rate reported here is similar to those already published for an axillary approach using a multiple injection technique, providing that an equivalent definition of the success was used. [16][17][18] This observation is important since it is recognized that compared with a multiple injection technique, a single injection technique may cause less pain and discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…4 On the basis of classical anatomical descriptions, we thought that the superficial ulnar nerve, if already blocked, could be exposed to nerve injury during localization of the deep radial nerve. Therefore we conducted this prospective, randomized study and compared two sequences: median, radial, ulnar, and musculocutaneous nerves vs median, ulnar, radial and musculocutaneous nerves in terms of ulnar nerve stimulation during the radial nerve localization and conversely.…”
Section: Objectif : Le Blocage Du Plexus Brachial Au Niveau Du Canal mentioning
confidence: 99%
“…3,4,6,7 In France, the number of regional anesthetic procedures has increased 14-fold between 1980 and 1996. 8 Because of this recent large increase it is mandatory to remain cautious when interpreting good results concerning the safety of the brachial plexus block through the humeral canal.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
See 1 more Smart Citation
“…1 9 Dargestellt sind typische Reaktionen nach einer Stimulation des N. medianus (a), N. ulnaris (b) und N. radialis (c). Die Pfeile geben die Richtung der induzierten Bewegung an ren, favorisieren einige Autoren Mehr fachstimulationstechniken [12,17].…”
Section: Axilläre Blockadenunclassified